Working for Justice in Argentina. (February 2021) - Sobering, Katherine
Worker-recuperated businesses, like the Hotel Bauen highlighted in this essay, are organizations that were closed by their private owners, occupied by their workers, and restarted as cooperatives. As the author learned over the course of her fieldwork, many were established not only to save jobs, but also to create better jobs. Studies of workplaces in the Global North often detail how workplace policies can lessen the degree or severity of unequal treatment. But some organizations guided by principles of democracy, justice, and self-management take a more radical approach: to actively promote equality at work.